The Impact of Non-performing Loans on Bank Profitability: Evidence from Türkiye - Kalkan, Göktürk (Public Governance, Administration and Finances Law Review, 2025)
Non-performing loans (NPLs) are widely recognised as key indicators of the health of banks and, by extension, the broader economy. This study examines the impact of NPLs on the profitability of banks in Türkiye from 2003 to 2020, using Return on Assets (ROA) as the primary profitability measure. Panel data from 15 deposit banks were analysed using a robust least squares regression (with M-estimation) to address outliers and heteroscedasticity. Key variables include the NPL ratio, ownership concentration (OC), bank size, deposit ratio, consumer price index (CPI) and gross domestic product growth rate. The analysis shows a significant negative relationship between NPLs and ROA, indicating that higher NPL levels are associated with lower ROA. OC and CPI also exhibit negative effects on ROA, whereas bank size, deposit ratio and GDP growth rate have positive impacts on profitability. These findings underscore the need for effective NPL management to maintain the financial health of banks. The results highlight the importance of internal management efficiency, macroeconomic stability and robust regulatory frameworks in improving bank profitability in Türkiye.